The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/dmcn.13352
|View full text |Cite
|
Sign up to set email alerts
|

Causes of mortality in individuals with tuberous sclerosis complex

Abstract: Renal disease is a major cause of mortality in TSC. Lifelong surveillance and early intervention is warranted. SUDEP is also an important cause of mortality. Patients with learning disabilities are at significantly greater risk of early mortality and this implies the need for greater vigilance for TSC-related complications in this group. Female patients are vulnerable to pulmonary and renal disease. Pancreatic lesions are a rare but potentially treatable cause of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 28 publications
(67 reference statements)
3
87
0
6
Order By: Relevance
“…The presence of LAM affected overall mortality; of the patients who had LAM, 40% (4 out of 10 patients) died, a higher proportion than any other organ involvement from TSC (Shepherd, Gomez, Lie, & Crowson, 1991). Another recent single-center experience from the UK reported similar findings where renal involvement from TSC was the most common cause of death, and LAM accounted for 12.5% (2 out of 16) of all TSC-related deaths in this cohort (Amin et al, 2017). In another study, 12.5% (6 out of 48) of the TSC-LAM patients progressed and died because of LAM (Cudzilo et al, 2013).…”
Section: Introductionsupporting
confidence: 70%
“…The presence of LAM affected overall mortality; of the patients who had LAM, 40% (4 out of 10 patients) died, a higher proportion than any other organ involvement from TSC (Shepherd, Gomez, Lie, & Crowson, 1991). Another recent single-center experience from the UK reported similar findings where renal involvement from TSC was the most common cause of death, and LAM accounted for 12.5% (2 out of 16) of all TSC-related deaths in this cohort (Amin et al, 2017). In another study, 12.5% (6 out of 48) of the TSC-LAM patients progressed and died because of LAM (Cudzilo et al, 2013).…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, the lethal seizure was also not longer than the very first seizure. Importantly, SUDEP is one of the leading causes of seizure‐related death and contributes substantial to the cause of death in patients who die from complications of TSC . Besides, SUDEP cases were described in 10% of the families who carried mutations in genes of the GATOR1 complex, a regulator of the mTOR pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Premature decline of glomerular filtration rate (GFR) occurs in ~40% of patients with TSC (Bissler & Kingswood, ; Kingswood, Bolton, et al, ), and can occur in the absence of angiomyolipomata bleeding or interventions and is, in part, due to the renal cystic disease (Janssens et al, ). The importance of renal disease in TSC is highlighted by two studies that showed it was the leading cause of death in those clinic populations (Amin et al, ; Shepherd & Gomez, ).…”
Section: Introductionmentioning
confidence: 99%